2022
DOI: 10.7185/geochemlet.2242
|View full text |Cite
|
Sign up to set email alerts
|

High latitude controls on dissolved barium isotope distributions in the global ocean

Abstract: The high latitude regions play a key role in regulating the marine biogeochemical cycling of barium (Ba) and the pre-formed Ba isotope compositions in the global ocean. In this study, we present 17 new depth profiles of dissolved Ba concentrations ([Ba]) and isotope compositions (δ 138 Ba) from the high latitude Atlantic, Pacific and Southern Oceans to trace the ventilation of deep waters in the Southern Ocean and their subsequent transport throughout the global ocean. Our data reveal how biogeochemical proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…(2010), stable Ba isotopes have been developed as a new tracer to investigate the (bio)geochemical cycling of Ba in marine environments. The majority of studies carried out so far have revealed measurable variations of dissolved Ba isotopic compositions in vertical seawater profiles and along the salinity gradient in estuaries (Bates et al., 2017; Bridgestock et al., 2018, 2021; Cao, Li, et al., 2020; Cao, Siebert, et al., 2020; Cao et al., 2016, 2021; Geyman et al., 2019; Hemsing et al., 2018; Horner et al., 2015; Hsieh & Henderson, 2017; Yu et al., 2022). Stable Ba isotopic signatures of the marine (as well as estuarine and fluvial) sedimentary solid phase are systematically lighter than seawater and vary within a relatively narrow range (Bridgestock et al., 2018, 2019; Charbonnier et al., 2020; Crockford et al., 2019; Nan et al., 2018; Nielsen et al., 2018; Scholz et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…(2010), stable Ba isotopes have been developed as a new tracer to investigate the (bio)geochemical cycling of Ba in marine environments. The majority of studies carried out so far have revealed measurable variations of dissolved Ba isotopic compositions in vertical seawater profiles and along the salinity gradient in estuaries (Bates et al., 2017; Bridgestock et al., 2018, 2021; Cao, Li, et al., 2020; Cao, Siebert, et al., 2020; Cao et al., 2016, 2021; Geyman et al., 2019; Hemsing et al., 2018; Horner et al., 2015; Hsieh & Henderson, 2017; Yu et al., 2022). Stable Ba isotopic signatures of the marine (as well as estuarine and fluvial) sedimentary solid phase are systematically lighter than seawater and vary within a relatively narrow range (Bridgestock et al., 2018, 2019; Charbonnier et al., 2020; Crockford et al., 2019; Nan et al., 2018; Nielsen et al., 2018; Scholz et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In general, δ 138 Ba and δ 30 Si display similar distributions in the ocean. Major rivers are characterized by relatively light isotopic signatures of both Ba (average ∼0.2‰) and Si (average ∼1.3‰), reflecting the dissolution of lithogenic materials, whereas surface seawater shows significantly heavier isotopic signatures of both Ba (0.3–0.6‰) and Si (up to 3–4‰) due to the preferential removal of the light isotopes via the processes described above (Bridgestock et al., 2021; Cao et al., 2021; Frings et al., 2016; Hsieh & Henderson, 2017; Sutton et al., 2018; Yu et al., 2022; Zhang, Cao, et al., 2020). Deep seawaters are typically enriched in isotopically light Si and Ba compared to the surface seawaters as a result of remineralization processes and water mass mixing (Bates et al., 2017; De Souza, Reynolds, Johnson, et al., 2012; De Souza, Reynolds, Rickli, et al., 2012; Horner et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the stable isotopic composition of Ba (δ 138 Ba) has been developed to investigate the variability of key aspects of marine Ba biogeochemistry, given that in the upper ocean light Ba isotopes are either preferentially incorporated during the precipitation of barite (Bridgestock et al., 2018; Cao et al., 2016; Horner et al., 2015, 2017; Yu et al., 2022) or preferentially adsorbed onto particles (Cao et al., 2020). Similarly, over the past two decades, the stable isotopic composition of Si (δ 30 Si) has been used as a tool to identify Si sources and to track Si biogeochemical cycling and Si utilization on various temporal and spatial scales given that silicifiers preferentially incorporate the lighter Si isotopes to build their silica skeletons or shells (cf., De La Rocha et al., 1997; Sutton et al., 2018).…”
Section: Introductionmentioning
confidence: 99%